Effects of mixing sequence on mechanical properties of graphene oxide and warm mix additive composite modified asphalt binder. (30th August 2019) - Liu, Kefei; Zhu, Juncai; Zhang, Kun; Wu, Junliang; Yin, Jian; Shi, Xianming
Highlights: Composite modified asphalt binder features good mechanical properties. Different GO and Sasobit® mixing sequences have significant effects on the performance of CMAB. Different GO and WCO mixing sequences have no significant effect on the performance of CMAB. GO is suggested to be added first in the preparation of CMAB. Abstract: In this work, the effects of mixing sequence of graphene oxide (GO) and warm mix additives on the mechanical properties of the composite modified asphalt binder (CMAB) were evaluated. The warm mix additives included Sasobit® and waste cooking oil (WCO). The experimental results indicated that the combination of GO and Sasobit® can greatly improve the high-temperature performance of asphalt, and the blending of GO and WCO can significantly enhance the fatigue and low-temperature properties of the asphalt. Statistical analysis results suggested that different GO and Sasobit® mixing sequences have significant influence on the workability, mechanical properties, and chemical reaction characteristics of the CMABs, while the influence of different GO and WCO mixing sequences on these properties of asphalt is not significant. In conclusion, GO is suggested to be added first to achieve the better performance of the nano-modified asphalt binder.